Characterizing Auroral‐Zone Absorption Based on Global Kp and Regional Geomagnetic Hourly Range Indices - R. A. D. Fiori; L. Trichtchenko; C. Balch; E. Spanswick; S. Groleau (Space Weather)
Abstract Increased ionization in the auroral oval leads to the absorption of high‐frequency radio waves in the auroral zone, or auroral absorption. Auroral absorption is typically characterized by global geomagnetic activity indices, such as the Kp index. In this paper the hourly range of the magnetic field (HR) is examined as an alternative to the 3‐hr Kp index for describing the dynamic and localized features of auroral absorption represented by the hourly range of absorption (HRA). Kp, magnetometer, and riometer data were examined for a 3‐year period for stations spread across typical auroral latitudes. A general linear relationship was shown to exist between Kp and LOG10(HRA) for Kp < 4; for Kp ≥ 4 the correlation was weaker. A stronger linear correlation was demonstrated between LOG10(HRA) and LOG10(HR) for HR > 50 nT, characterized by a correlation coefficient of R = 0.63. Increased variability in the relationship between HRA and Kp was attributed to the following factors: the variability of the magnetic field within the 3‐hr window characterized by the Kp index, which was better represented by a 1‐hr HR; the dependence of the Kp index on subauroral magnetic data, which is not subject to the geomagnetic variations typically experienced within the auroral region; and reduced statistics for Kp > 6.